ENT 300 Fundamentals of Entrepreneurship B.A.H.M2 Lounge Café / Abang Muhamad Zulfadhli... [et al.] - Abang Ariffin, Abang Muhamad Zulfadhli; Basusie, Brian Melchior; Sapenee, Mohd Kassim; Ismail, Muhammad Arif; Uri, Halerry Chundang (2013)
The combination of the first capitalist letter from our names has created a name for our company that is BAHM 2 Lounge Cafe. The form of our business is franchises which are consist of five members. Even though we get a business loan from the bank, each of also contributes certain amount of capital as agreed in the partnership agreement. The main business activity of BAHM2 Lounge Cafe is to provide food and beverage services that only focus on light foods and hot and cold drinks which are variable types of it. We have design our premises according to theme that we have agreed which will make our future customers feel relax and chill without thinking too much. Even our business name is BAHM 2 Lounge Cafe, but it is not really a lounge that is for the upper level people. It is only a name in the papers but a café in the practices; so, it is for all individuals or groups to hang up around there. Every single of our member have their own part or their own position in the business plan and there are no sleeping partners and all of us entitled to participate in the business management. As agreed before, that Abang Muhamad Zulfadhli Bin Abang Ariffin will hold the position as the General Manager, Halerry Chundang Ak Uri as the Administration Executive, Brian Melchior Basusie as the Operational Executive, Mohd Kassim Bin Sapenee as the Marketing Executive, and Muhammad Arif Bin Ismail as the Financial Executive. The selection of each position is based on the leadership, experiences, skills, capabilities and abilities. If specifically focusing on each position, the General Manager is responsible in planning, organizing, leading, and controlling the business. As for the Administration Executive, he is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operational Executive is responsible to the entire job that related to the operation and will supervise and coordinate the operation of the business, and for the Marketing Executive will have the responsibility to create the marketing plan, identifying the customer's need and demand, identifying the competitors, target market, market size and forecast the future market. Lastly, the Financial Executive will be responsible for preparing the budget, financial expenses and the flow of the money of the organization.